The daytime trapped lee wave pattern and evolution induced by two small‐scale mountains of different heights. (2nd April 2022) - Xue, Haile; Giorgetta, Marco A.; Guo, Jianping
Abstract: Two large‐eddy simulations are carried out to investigate the vertical structure and daytime evolution of trapped lee waves (TLWs) triggered by mountains of two heights (500 and 1500 m, denoted as HM500 and HM1500, respectively) based on a typical subtropical winter troposphere, in which a steady upper‐level jet and a clear diurnal evolution of the atmospheric boundary layer (ABL) are present. Multimode TLWs co‐exist at three altitudes with dominant wavelengths increasing with altitude in HM500, while a single‐mode TLW dominates throughout most of the troposphere in HM1500. The wave amplitudes for both experiments increase from midday, reaching peaks in the afternoon, likely related to the reduction of the wave absorption by the ABL. Whereas the growth of the dominant wavelength of TLWs with time is mainly limited to layers near the ABL top for HM500; the dominant wavelength in HM1500 stays steady with time. The TLW pattern and evolution can be largely explained by linear theory. In HM500, the multimode pattern is due to the perturbation source at a low altitude where high wavenumbers are supported, and the wavelength lengthening near the ABL top can be explained by the decreasing Scorer parameter in the afternoon. In HM1500, the large‐amplitude single‐mode TLW is due to the enhanced and elevated perturbation source of the higher mountain where the Scorer parameter is smaller and affected less by the ABL. The continual amplification of the dominant TLW in HM1500 may be caused by the instability from the wave‐induced momentum deficit at the upper ABL, which further facilitates the wave propagation. Our findings are beneficial for improving our process‐scale understanding of the vertical structure and diurnal evolution of TLWs constrained by the upper‐level jet and ABL evolution, and have implications for improving orographic gravity‐wave parameterization especially when the model resolution approaches around 10 km. Abstract : Multiple‐ and single‐mode trapped lee waves (TLWs) are found in the lee of low and high mountains, respectively, when the upper‐level jet (ULJ) is present. TLWs are amplified in the afternoon for both mountain heights due to the release of wave absorption from the stable to the convective boundary layer (S/CBL). The large‐amplitude TLWs forced by high mountains may induce downslope windstorms (DSW) and rotors (R), and propagate further downstream due to the self‐induced ABL instability in the afternoon.